Financial Inclusion and Income Improvement of UMKM in Indonesia: An Analysis - Lia Nazliana Nasution; Bakhtiar Efendi; Rizkil Khoir (Proceeding of The International Conference on Business and Economics, 2024)
The aim of this study is to analyze the simultaneous effects of financial inclusion, financial literacy, MSME investment, and unemployment on MSME income and the unemployment rate in Indonesia. We used a simultaneous equation method with the observed variables being financial literacy, financial inclusion, the number of MSMEs, MSME labor, MSME investment, MSME income, and unemployment. The data used is secondary data covering the period from 2011 to 2022. The results show that the variables of financial inclusion, financial literacy, MSME investment, and unemployment have a significant partial and simultaneous effect on MSME income. From the equation, financial inclusion, financial literacy, and MSME investment have a positive effect on MSME income, while unemployment has a negative effect on MSME income. Furthermore, the variables of the number of MSMEs, MSME labor, and MSME income have a significant partial and simultaneous effect on unemployment. From the equation, the number of MSMEs, MSME labor, and MSME income have a negative effect on unemployment.